Nutritional Genomics : The impact of dietary regulation of gene function on human disease - Bidlack, Wayne R; Ed. Rodriguez, Raymond L (CRC Press, 2012)
Nutritional Genomics: The Impact of Dietary Regulation of Gene Function on Human Disease.